1967
DOI: 10.1083/jcb.35.1.237
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Denucleation in Circulating Erythroblasts

Abstract: Erythroblast denucleation in the peripheral blood was studied by electron microscopy. Blood was used from dogs anemic either by infection with Babesia canis or from injections of phenylhydrazine hydrochloride. One of the earliest stages of denucleation was the migration of nuclei to the plasmalemma. Mitochondria and coalesced vesicles, derived from the cell membrane of the erythroblast, congregated at the underside of the nuclear envelope unapposed by erythroblastic cell membrane. The coalesced vesicles appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

1968
1968
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 10 publications
(16 reference statements)
3
56
0
Order By: Relevance
“…7 A recent study by Keerthivasan et al using primary mouse and human erythroblasts supported the hypothesis that vesicle trafficking and subsequent vacuole coalescence provide additional membrane for the separating nucleus and reticulocyte. 8,9 Actin polymerization was again seen to play a role by Ji et al who found that Rac GTPase deregulation by overexpression of either dominant negative or constitutively active mutants of Rac1 or Rac2 or by pharmacologic inhibition by the Rac-specific inhibitor NSC23766 10,11 decreases enucleation of mouse fetal liver erythroblasts in culture. Moreover, down-regulation of mDia2, a downstream effector of Rho GTPases, by small interfering RNA (siRNA) blocks erythroblast enucleation.…”
Section: Introductionmentioning
confidence: 99%
“…7 A recent study by Keerthivasan et al using primary mouse and human erythroblasts supported the hypothesis that vesicle trafficking and subsequent vacuole coalescence provide additional membrane for the separating nucleus and reticulocyte. 8,9 Actin polymerization was again seen to play a role by Ji et al who found that Rac GTPase deregulation by overexpression of either dominant negative or constitutively active mutants of Rac1 or Rac2 or by pharmacologic inhibition by the Rac-specific inhibitor NSC23766 10,11 decreases enucleation of mouse fetal liver erythroblasts in culture. Moreover, down-regulation of mDia2, a downstream effector of Rho GTPases, by small interfering RNA (siRNA) blocks erythroblast enucleation.…”
Section: Introductionmentioning
confidence: 99%
“…The loss of the intermediate filaments allows the nucleus to move freely to the periphery of the cell and occupy an acentric position prior to enucleation. A number of studies have proposed that enucleation may be a process similar to cytokinesis (Campbell, 1968;Repasky and Eckert, 1981a,b,c;Simpson and Kling, 1967;Danon, 1967, 1970) and have suggested that F-actin is present in the form of a ring in the constriction, similar to the cleavage furrow of mitotic cells (Perry et al, 1971;Schroeder, 1973). Using splenic erythroblasts from mice infected with the anemia-inducing strain of Friend virus, Koury et al (1989) showed that F-actin is concentrated between the extruding nucleus and incipient reticulocyte in enucleating erythroblasts.…”
Section: Enucleation Of Primitive and Definitive Erythrocytesmentioning
confidence: 99%
“…During enucleation, the erythroblast extrudes its nucleus tightly apposed to the plasma membrane, forming a reticulocyte (Ihle and Gilliland, 2007;Koury et al, 2002;Richmond et al, 2005). Pioneering studies using electron microscopy revealed that at the earliest stage of enucleation the erythroblast nucleus becomes located close to the cell membrane away from the center of the cell (Simpson and Kling, 1967;Skutelsky and Danon, 1967) and that a cytokineticlike furrow is formed in the region between the extruded nucleus and the incipient reticulocyte (Koury et al, 1989;Skutelsky and Danon, 1967). Actin filaments (F-actin) accumulate in the cytokinetic-like furrow (Ji et al, 2008;Koury et al, 1989) and disruption of F-actin (Ji et al, 2008;Koury et al, 1989;Yoshida et al, 2005) or depletion of mDia2, a regulator of actin polymerization (Ji et al, 2008), blocked enucleation, suggesting that actin-based forces drive nuclear extrusion.…”
Section: Introductionmentioning
confidence: 99%